Elective Delivery versus Expectant Management for Gastroschisis: A Systematic Review and Meta-Analysis - Chen, Yong; Zhao, Jiashen; Alganabi, Mashriq; Mesas-Burgos, Carmen; Eaton, Simon; Wester, Tomas; Pierro, Agostino (European Journal of Pediatric Surgery, 2022)
Introduction The optimal timing of delivery for pregnancies complicated by prenatally diagnosed gastroschisis remains controversial. Therefore, the aim of this study was to find whether elective or expectant delivery is associated with improved neonatal outcome.Materials and Methods MEDLINE and Embase databases were searched for studies up to 2021 that reported timing of delivery for prenatally diagnosed gastroschisis. A systematic review and meta-analysis were then performed in group 1: moderately preterm (gestational age [GA]: 34–35 weeks) elective delivery versus expectant management after GA 34–35 weeks; and group 2: near-term (GA: 36–37 weeks) elective delivery versus expectant management after GA 36–37 weeks. The following clinical outcomes were evaluated: length of stay (LOS), total parenteral nutrition (TPN) days, bowel morbidity (atresia, perforation, and volvulus), sepsis, time of first feeding, short gut syndrome and respirator days, and mortality.Results Two randomized controlled trials (RCT)s and eight retrospective cohort studies were included, comprising 629 participants. Moderately preterm elective delivery failed to improve clinical outcomes. However, near-term elective delivery significantly reduced bowel morbidity (7.4 vs. 15.4%, relative risk = 0.37; 95% confidence interval [CI]: 0.18, 0.74; p = 0.005; I2 = 0%) and TPN days (mean difference =−13.44 days; 95% CI: −26.68, −0.20; p = 0.05; I2 = 45%) compared to expectant delivery. The mean LOS was 39.2 days after near-term delivery and 48.7 days in the expectant group (p = 0.06).Conclusion Based on the data analyzed, near-term elective delivery (GA 36–37 weeks) appears to be the optimal timing for delivery of pregnancies complicated by gastroschisis as it is associated with less bowel morbidity and shorter TPN days. However, more RCTs are necessary to better validate these findings.
Keywords: gastroschisis; elective delivery; expectant management; meta-analysis